Chronic cervicitis in women of reproductive age: pathogenesis and treatment. A review - Vera N. Prilepskaya; Angelina A. Odyvanova; Elena A. Mezhevitinova (IP Berlin A.V., 2023)
The issue of cervicitis and vulvovaginitis is relevant worldwide due to the increasing incidence in women of reproductive age. To date, the significant role of chronic cervicitis in the development of cancer and other diseases of the reproductive system, including cervical cancer, has been proven. In recent years, a number of large studies have been conducted, covering a significant part of the clinical issues, pathogenesis, and epidemiology of cervicitis. However, there is a clear need for further studies of both the etiological factors and the pathogenetic mechanisms of inflammatory cervical disease to support the treatment choice.